(3GdOYGA GdeSJLGHs
(3ChdgG (B:s
(3SHMGfc jG eHOY GdCTjGA dG ef TjA cGf s
(3BNQgG (B:s
(3Je GdOYGA hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: 16s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3dYdgG dYdj Hf MeRI GdOhQRjs
(3QGLY eG bHdg HGdeLehY s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJhMjO hGdedd hGdfMds